2008
DOI: 10.1093/europace/eun001
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of oesophageal wall injury post-pulmonary vein antrum isolation for treatment of patients with atrial fibrillation

Abstract: A significant number of patients experienced oesophageal wall injury post PVAI. Initiating PPIs in this group of patients might facilitate recovery of oesophageal wall injuries caused by radio-frequency energy delivery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
109
2
5

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 149 publications
(118 citation statements)
references
References 26 publications
2
109
2
5
Order By: Relevance
“…The absence of mucosal changes in the present study is possibly due to a different ablation strategy and the use of conscious sedation rather than general anesthesia or deep sedation. Schmidt et al 11 reported esophageal wall changes in 47% of their patients using either an 8-mm solid-tip ablation catheter or a 3.5-mm tip open irrigated catheter with a maximum power setting of 50 W. This high power, compared with our study, may lead to deeper ablation lesions affecting also the esophageal mucosa. Mediastinal changes were not investigated in that study.…”
Section: Zellerhoff Et Al Esophageal and Mediastinal Changes After Pvimentioning
confidence: 41%
“…The absence of mucosal changes in the present study is possibly due to a different ablation strategy and the use of conscious sedation rather than general anesthesia or deep sedation. Schmidt et al 11 reported esophageal wall changes in 47% of their patients using either an 8-mm solid-tip ablation catheter or a 3.5-mm tip open irrigated catheter with a maximum power setting of 50 W. This high power, compared with our study, may lead to deeper ablation lesions affecting also the esophageal mucosa. Mediastinal changes were not investigated in that study.…”
Section: Zellerhoff Et Al Esophageal and Mediastinal Changes After Pvimentioning
confidence: 41%
“…Some of the well-identified UGI system complications, including atrioesophageal fistulae, esophageal ulcerations, gastroesophageal reflux, acute pyloric spasm, and gastric hypomotility, are at least partially a consequence of VN injury. [3][4][5][6][7][8][9][10][11] Because the consequences of UGI injury can be catastrophic, the importance of understanding the effect of AF ablation on VN injury cannot be overstated.…”
Section: Discussionmentioning
confidence: 99%
“…Some of the reported UGI complications resulting from AF ablation include atrioesophageal fistulae, esophageal mucosal ulcerations with or without bleeding, gastroesophageal reflux, pyloric spasm, and gastric hypomotility. [3][4][5][6][7][8][9][10][11] The exact mechanism of these injuries is not known; however, injury to the vagus nerve (VN) and its components are proposed to be one of the major players in many of these complications. 5,10 The VN because of its close proximity to the posterior wall of the LA is susceptible to the thermal injury from RFA.…”
mentioning
confidence: 99%
“…Therefore, it is possible that microbubble formation is not a consistent marker of tissue overheating (68). Microbubble formation may even have the same problem as luminal temperature monitoring by a latency time too long to stop energy delivery and prevent EU, especially when showers of microbubbles occur (28,66). In contrast to another study published, we did not show any increased risk of general anesthesia versus deep sedation (2.7% vs. 2.2%) (61).…”
Section: Identification Of a High-risk Population For Esophageal Injucontrasting
confidence: 71%
“…In addition, power does not correlate with esophagus temperature, and overheating even occurs when the ablation site is quite distant (31). The additional usage of intracardiac echocardiography (ICE) gives divergent study results (28,63,66). Cummings et al (63) reported good correlation of microbubble formation and esophageal temperature increase.…”
Section: Identification Of a High-risk Population For Esophageal Injumentioning
confidence: 99%